Histopathological Effects of Ageratum Leaf Extract (Ageratum Conyzoides) on Wound Healing Acceleration After Acute Excisional Wound on Epidermis in Type 2 Diabetes Mellitus Model of Sprague Dawley Rats (Rattus norvegicus) (Majalah Kedokteran Bandung, 2019)
Diabetic wound healing problem often occurs if proper care is not given which will lead to the development of a chronic wound. Ageratum (Ageratum conyzoides L.) leaves is one of the most common plants in tropical areas, including Indonesia, which are frequently used in traditional treatment due to its anti-bacterial properties. This experimental study aimed to identify the effects of topical application of Ageratum leaf extract on wound healing based on histopathological examination of the reepithelization, ulceration, neovascularization, and the presence of inflammatory cells. This study was performed in the period of September to December 2017 at the Pharmacology and Pathology Anatomy laboratories of Dr. Hasan Sadikin General Hospital Bandung, Indonesia. Excisions were made on the back of the 36 rats that were divided into control and test groups. The test group then received a topical application of Ageratum leaf extract. The resulting histopathologic appearance of the wound was then examined. The test group showed better wound healing in all parameters inspected when compared to the control group. Mann-Whitney Test with 95% confidence interval (p
Keywords: Ageratum leaves; diabetic wound; wound healing